Analyse de l’adéquation des matières de la compréhension orale du site Le Point du FLE comme matières pédagogiques alternatives pour le cours de français oral élémentaire - Rizkiyana Ayuningtyas; Tri Eko Agustiningrum (Didacticofrancia Journal Didactique du FLE, 2026)
This research aims to find out how much A1/A2 level listening material is contained in the Le Point du Fle website. After that, we analyze its suitability for use as supporting teaching material in the Français Oral Élémentaire course. The research used a descriptive qualitative approach, and data were collected in the form of audio or video recordings using the documentation method. Based on the documentation, there are 7 audio and video documents for listening skills. The technique used to analyze the data uses data cards based on the Semester Learning Plan (RPS) for the Français Oral Élémentaire course. The analysis shows 7 listening documents at the A1/A2 level, spread across 6 menus. Of the 7 audio and video documents, support the achievement of course learning outcomes (CPMK) 1, 4, 5, 7, 9, and 11. As for CPMK 2, 3, 6, 8, 10, and 12, there are no supporting documents.